The Allelopathic Effects of Scots Pine (Pinus sylvestris L.) Leaf Extracts on Turf grass Seed Germination and Seedling Growth - BULUT, YAHYA; DEMIR, METIN (Asian Journal of Chemistry, 2010)
Allelopathic effects of aquous extracts of 10, 20, 30, 40 and 50 g/L dry Scot pine (Pinus sylvestris) leaves on seed germination and seedling growth of 4 turf grass varieties were investigated. All the concentration extracts tested had significantly inhibitory effects on seed germination percentage of Lolium perenne var. Ovation, Festuca rubra rubra var. Franklin, Festuca rubra commutata var. Koket and Festuca ovina var. crystal compared with the control. This inhibition effect increased with increasing Scot pine extract concentration. The treatments of 20, 30, 40 and 50 g/L concentration on hard fescue showed no germination. However, 10 g/L treatment of leaf extracts promoted root elongation on perennial ryegrass and shoot elongation on strong creeping red fescue, compared with the control. The average time of germination (ATG) and the time to 50 % of the final germination (GT50) were significantly reduced by the extracts in comparison with the distilled water control.